Stateness and democracy in East Asia - Croissant, Aurel; Hellmann, Olli (Cambridge University Press, 2022)
Democratization and state building are fundamental political processes, yet scholars cannot agree on which process should be prioritized in order to put countries on a positive path of institutional development. Where much of the existing literature on the state-democracy nexus focuses on quantitative cross-national data, this volume offers a theoretically grounded regional analysis built around in-depth qualitative case studies. The chapters examine cases of successful democratic consolidation (South Korea, Taiwan), defective democracy (Philippines, Indonesia, East Timor), and autocratic reversal (Cambodia, Thailand). The book's evidence challenges the dominant 'state first, democracy later' argument, demonstrating instead that stateness is neither a sufficient nor a necessary condition for democratic consolidation. The authors not only show that democratization can become trapped in path-dependent processes, but also that the system-level organization of informal networks plays a key role in shaping the outcome of democratic transitions.
Literaturhinweise, Register
Keywords: East Asia -- Politics and government -- 21st century; Demokratisierung; Ostasien